2018
DOI: 10.1002/fam.2506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural weathering on the fire properties of intumescent fire‐retardant coatings

Abstract: Summary Fire‐retardant coatings could be one option for providing enhanced protection to buildings during a wildfire, particularly when applied to combustible siding and in under‐eave areas. Limited studies have been conducted on their effectiveness but maintaining adequate performance after weathering has been questioned. This paper reports on a study evaluating the effect of natural weathering on the performance of intumescent‐type fire‐retardant coatings. The main concerns were (a) the reduction of ignition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Some examples of these short-term strategies could comprise of protecting structures from ignition and decreasing fire spread within a community. The short-term mitigation approaches can be divided into active (e.g., extinguishers and sprinklers) and passive (e.g., pre-applied water, gel, or foam wetting agents or fire resistance coating and composite layers) fire protection methods [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of these short-term strategies could comprise of protecting structures from ignition and decreasing fire spread within a community. The short-term mitigation approaches can be divided into active (e.g., extinguishers and sprinklers) and passive (e.g., pre-applied water, gel, or foam wetting agents or fire resistance coating and composite layers) fire protection methods [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The current market offers many FRCs (film-forming and stain) to protect wood-based materials for outdoor applications. A few comparative studies have been performed on commercial FRCs' fire retardancy and/or weathering performances which mostly show that the weathering exposure is decreasing the effectiveness of fire protection of intumescent coatings [17,24]. For weathering, coatings can be exposed to temperature, humidity, freezing cycles, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some intumescent coatings exhibit poor paint properties, as is reported in Mariappan, 18 and especially the water-based systems are sensitive to weathering, as is reported in the literature 3,18,19 and examined in Maciulaitis et al 2 and Bahrani et al 22 The high polarity of the ingredients causes poor compatibility with the coating resin or polymer matrix of the binder. 19 Under natural conditions, humidity, temperature, and solar radiation cause aging of the composite and may lead to the reduction of fire resistance.…”
Section: Introductionmentioning
confidence: 84%
“…These coatings can swell 20 to 50 times their original thickness, forming a carbonaceous-rich layer between the substrate material and heat source. A study reported that weathering drastically reduced their effective service life of the intumescent coating much less than that reported in the product marketing literature [2].…”
Section: Introductionmentioning
confidence: 87%